2015
DOI: 10.12688/f1000research.5732.2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition transition in South Asia: the emergence of non-communicable chronic diseases

Abstract: Overview: South Asian countries have experienced a remarkable economic growth during last two decades along with subsequent transformation in social, economic and food systems. Rising disposable income levels continue to drive the nutrition transition characterized by a shift from a traditional high-carbohydrate, low-fat diets towards diets with a lower carbohydrate and higher proportion of saturated fat, sugar and salt. Steered by various transitions in demographic, economic and nutritional terms, South Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 42 publications
1
37
1
Order By: Relevance
“…The nutrition transition implies moving from a traditional diet which is high in carbohydrate and fibre and low in sugar and fat to a more contemporary Western diet which is high in fats, saturated fats, sodium and sugar [11]. One of the main drivers of this transition is urbanization [10,12].A recent review of dietary studies in developing countries by Ochola and Masibo showed what the typical dietary scenario in developing countries is [13]. This review included 50 studies from 42 countries in children and adolescents.…”
mentioning
confidence: 99%
“…The nutrition transition implies moving from a traditional diet which is high in carbohydrate and fibre and low in sugar and fat to a more contemporary Western diet which is high in fats, saturated fats, sodium and sugar [11]. One of the main drivers of this transition is urbanization [10,12].A recent review of dietary studies in developing countries by Ochola and Masibo showed what the typical dietary scenario in developing countries is [13]. This review included 50 studies from 42 countries in children and adolescents.…”
mentioning
confidence: 99%
“…The demography of Bangladesh is usually characterised by total fertility rate (TFR) and maternal and child mortality (MCM) [1,2]. Like all other south Asian nations, widespread poverty, poor healthcare infrastructure, inequality in access to care, and low health literacy constitute some of the major causes of underutilization of essential maternal healthcare services (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, developing regions, especially South Asia and sub-Saharan Africa, are lagging behind the rest of the world in their capacity to put this knowledge into practice (Bishwajit 2015). Initiatives led by the maternal health-related millennium development goal (MDG) 5 initiative saw a 34% decline in MMR since 1990 (Dynes et al 2013).…”
Section: Introductionmentioning
confidence: 99%